Halocyclobutanol Dehydration En Route to Halocyclobutenes - Oeser, Petr; Petrenko, Artem; Edlová, Tereza; Čubiňák, Marek; Koudelka, Jakub; Tobrman, Tomáš (Synthesis, 2022)
A new method for the preparation of halocyclobutenes is described. The developed process involves the dehydration of halocyclobutanols by using tetrafluoroboric acid–diethyl ether complex in dichloromethane at room temperature. The process allows for high yields of halocyclobutenes to be achieved by using alcohols that do not trigger the formation of isomeric allylic halides.
Keywords: elimination; alkenes; Grignard reaction; halohydrins; tetrafluoroboric acid–diethyl ether complex